ANALISIS PEMAHAMAN KONSEP MATEMATIKA SISWA PADA MATERI TEOREMA PHYTAGORAS DITINJAU DARI MOTIVASI BELAJAR KELAS VIII SMP NEGERI 1 LOLOFITU MOI - Rahmat Penius Halawa (Universitas Nias Raya, 2024)
This research aims to describe students' ability to understand concepts and learning motivation, especially regarding the Pythagorean theorem material. This research uses this type of research Qualitative with a descriptive approach. The informants in this research were class VII students at SMP Negeri 1 Lolofitu Moi with a total of 20 students. Data were analyzed using the steps of data collection, data reduction, data presentation, and drawing conclusions. The instruments in this research were concept understanding ability tests, questionnaires, and interviews. Based on the results of the research and discussion, the researcher concluded that class VIII students at SMP Negeri 1 Lolofitu Moi had different abilities in understanding concepts and students' learning motivation. In the concept understanding test it is in the poor category. The results of the test research show that the intrinsic motivation category is in the high and medium categories. Meanwhile, the results of the extrinsic motivation questionnaire were in the high and medium categories. The researchers' findings showed that they were unable to carry out mathematical manipulations; students are unable to draw conclusions, compile evidence, provide reasons or evidence for the truth of the solution, students are unable to draw conclusions from statements; and students are unable to draw patterns or properties of mathematical phenomena to make generalizations. Meanwhile, regarding learning motivation, most students are not yet able to study independently. Through this research, it is suggested that the emphasis on learning should not only be on outcomes, but more on processes related to students' ability to understand concepts and learning motivation.